Effect of S levels, methods of its application and irrigation schedule on growth, yield and water use by lentil (Lens culinaris) - SINGH, Y P; CHAUHAN, C P; GUPTA, RAJ K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment on lentil (Lens culinaris L.) was carried out during winter season (rabi) of 1992-93 and 1994-95 ondeficient sandy loam soil. The growth yield of lentil was markedly improved with the application of sulphur up to 40 kg/hawith placement method, whereas up to 60 kg S/ha applied as broadcast with 2 irrigations. The grain yield increased by 64.8and 55.1% with the application of 40 kg S/ha through placement and 60 kg S/ha through broadcast respectively. Themaximum water-lise (19.3 cm) and water-usc efficiency (61.9 kg grain/cm/ha) was recorded with 40 kg S/ha. The water-lisewas highest (25.2 cm) with 2 irrigation followed by 1 irrigation (18.8 cm) compared to rain fed (12.6 cm).